MATHEMATICS TEACHERS' KNOWLEDGE OF STUDENT THINKING AND ITS EVIDENCES IN THEIR INSTRUCTION - Çelik, Aytug Özaltun; Güzel, Esra Bukova (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2017)
The aim of this case study is to examine mathematics teachers’ knowledge of students’ thinking and its evidences in their teaching. The participants were three secondary mathematics teachers. Data were gathered from interviews and observations. While analyzing the data, the framework about teachers’ knowledge of students’ thinking was used. The findings showed that each teacher mainly considered the knowledge of students’ thinking as knowing students’ prior knowledge. They expressed that they benefited from the questions to reveal students’ ideas, encouraged their students to use different solution ways for the problems, and had ideas on misconceptions and difficulties their students might be confronted. The participants also considered students’ prior knowledge in their lessons, but they did not tackle their difficulties, errors and misconceptions unless students asked questions to them. They had the limited approaches for building on students’ mathematical ideas, promoting students thinking mathematics, triggering and considering divergent thoughts, engaging students in mathematical learning, and motivating students learning.